Aplicação da resistografia na estimativa da densidade e umidade da madeira em árvores jovens de eucalipto - Silva, João Gabriel Missia da (2019)
The drilling resistance technique have great potential operational to predict the wood properties of eucalyptus young trees, however, there are some factors that need to be better understood to increase their use. The aim of this study was to evaluate the parameters influencing the drilling resistance (DR) of the resistograph and the estimation of specific gravity and moisture content of the wood of eucalyptus clones at young age. DR readings were made with the resistograph (R650-SC) in the DBH (1.30 m from the ground) of 80 trees of two clones of Eucalyptus grandis x Eucalyptus urophylla (76 months of age), planted in Aracruz, Espírito Santo State, Brazil. DR was related to tree growth and wood formation characteristics, moisture content, apparent density profiles by X-ray densitometry and different drilling depths, and was also used as a predictive variable of natural moisture (M%) and specific gravity (SG) of wood. The relationship between DR and SG of wood with growth variables of trees was specific for genetic material. The diameter and wet mass of the trees, the lowest heartwood ratio and the highest sapwood thickness increased DR. In the first 24 months of growth and along the heartwood diameter, there was a rapid increase in SG and DR and the reduction of M%. The variability of these properties increased in sapwood formed in recent ages. The DR measured in standing trees corresponded to the densitometry profiles, and accurately estimated SG and M% of the wood. The 1.5 cm drilling depth from the bark was more accurate in SG estimation than the radial and diametric drilling of the clones’ trees. Between bands above the fibers saturation point and in equilibrium hygroscopic, the increase in the moisture content of the wood resulted in a higher DR. The use of DR as a response variable of wood quality and not only as a predictor of SG and M%, will contribute to its continuous monitoring, during the growth of the trees.